(untitled) (Revista Brasileira de Contabilidade e Gestão, 2014)
Home automation systems have increasingly attracted users in search of comfort and technology. However, commercially available solutions have a high cost and a complex installation process. The proposed solution aims to reduce the cost of home automation solutions and to facilitate the use of the system, both in the installation process and on the way to interact with the system, allowing the user to use the system on any device with web browser and internet connection.